Analisa Dampak Implementasi Odoo ERP: Studi Kasus Perusahaan Ready-Mixed Concrete PT. X - Eveline Cynthia Irawan; Yulia Yulia; Henry Novianus Palit (Jurnal Infra, 2020)
In this developing technological era, information technology has played an important role in the business world. However, PT. X is a ready-mixed concrete company that still does all the works manually. This causes the company to need more time to get the information needed because the company’s data are not integrated. In addition, there are human error problems that can occur due to employees’ negligence, such as forgetting to ask for proof of payment or forgetting to collect past due customer receivables. If the human errors are not immediately handled, they may cause problems in the company’s cash flow. This research tries to overcome the problems faced by PT. X by creating an Enterprise Resource Planning program. Among many ERP program platforms, Odoo was chosen as an ERP program that has many advantages, one of which is the ease in configuring and customizing the modules. An analysis of the ERP program is also carried out to measure the success of its implementation in the company by analyzing the suitability of business processes between the ERP program and the company's old business processes. Based on the analysis of the implementation of the ERP program at PT. X, it can be concluded that the ERP program has a positive impact on the company. Almost all business process designs in the Odoo program can meet the needs of the company well. Despite the limitations of Google Maps and financial data, the Odoo program can still run well.